Still a long journey to decentralize geopolitics. Issue 2 (July 2021) - An, Ning; Sharp, Jo; Shaw, Ian
In this brief response paper, we respond to the insightful commentaries that critically engage with our original article in this forum. First, we discuss whether Confucian culture is fundamental to Chinese geopolitics, emphasizing how and why culture is part of a wider epistemic resource. We also note that our model is not normative, but an analytic framework for understanding complex non-western situations. Second, we discuss the geographies and scales of our model, noting a core tension between geopolitics at the state level and in everyday life. Third, we address the 'gap' between theory and practice under our Confucian model, noting that there is often a strategic inclusion (or exclusion) of Confucianism in practice. We finish by emphasizing that our paper is part a longer journey to further decentralize the western hold upon geopolitics.